Dog Man Unleashed - Pilkey, Dav; Garibaldi, Jose (New York, NY Graphix, 2017)
Dog Man, the newest hero from the creator of Captain Underpants, is still learning a few tricks of the trade. If only the Chief would throw him a bone every once and a while ... Dog Man needs to dry up the drool, dust away the dander, and roll out of the refuse if he's going to impress the Chief, and he needs to do it fast! Petey the cat is out of the bag, and his criminal curiosity is taking the city by storm. Can the canine crime biter unleash justice on this ruffian in time to save the city, or will Petey get away with the purrfect crime?
"Tree House Comix proudly presents."
320L
104517
Keywords: Dogs -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Police -- Comic books, strips, etc; Dog Man (Fictitious character) -- Juvenile fiction; Cartoons and comics; Adventure and adventurers -- Juvenile fiction; Humorous stories. -- Juvenile fiction; .; Graphic novels; Comic books, strips, etc; Humorous comics